INTRODUCTION - H. Van der Westhuizen (Acta Theologica)
In this collection of articles, the authors reflect on justice and beauty. The question is: Why do the authors reflect on, or were asked to again reflect on justice, or more particularly, why on beauty? Why justice and why beauty, and not, for example, ethics and aesthetics? The answer, of course, depends on how justice and beauty are defined.